2020
DOI: 10.1111/bjh.16342
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment variability and clinicopathological characteristics on survival in patients with Epstein‐Barr‐Virus positive diffuse large B cell lymphoma

Abstract: Patients with EBV-positive diffuse large B cell lymphoma not otherwise specified (EBV + DLBCL (NOS)) recurrently present with advanced age and reduced performance status. They are therefore insufficiently represented in clinical trials and treatment is likely to differ. Here we assess clinicopathological characteristics, therapeutic variability and clinical outcome in the largest consecutively diagnosed EBV + DLBCL (NOS) cohort published to date (n = 80; median age 70 years; range 19-90). Centralized and syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
2
17
1
Order By: Relevance
“…And, CD30 expression is increased in patients with EBV+ DLBCL (43% vs 16% in EBV‐negative DLBCL) and has been associated with worse OS . Similar results were found in a German study, in which EBV+ DLBCL patients had a high incidence of CD30 expression (75%), and lack of expression of CD30 was associated with an improved survival . Survivin affects cellular apoptosis through indirect mechanisms that lead to inhibition of caspase 9 .…”
Section: Risk Stratificationsupporting
confidence: 77%
“…And, CD30 expression is increased in patients with EBV+ DLBCL (43% vs 16% in EBV‐negative DLBCL) and has been associated with worse OS . Similar results were found in a German study, in which EBV+ DLBCL patients had a high incidence of CD30 expression (75%), and lack of expression of CD30 was associated with an improved survival . Survivin affects cellular apoptosis through indirect mechanisms that lead to inhibition of caspase 9 .…”
Section: Risk Stratificationsupporting
confidence: 77%
“…Clinical data 1. Most samples of the current study were previously investigated for the impact of treatment variability and clinicopathological baseline characteristics on clinical outcome in EBV + DLBCL (NOS) 10 .…”
Section: Clinical Characteristics Of the Study Groupmentioning
confidence: 99%
“…Although recent observations relativized EBV as an independent risk factor, several studies found EBV + DLBCL (NOS) patients to be significantly enriched for adverse confounding clinical factors, such as stage, impaired performance status, advanced age, and significant canonical and alternative nuclear factor κB (NFκB)-pathway activation 10 . Altogether this resulted in a high number of cases with non-germinal center B-cell-like immunophenotype 2,7,[11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Previous clinicopathological studies emphasized the role of MYCrearrangement status while a systematical assessment of clinical implications regarding MYC amplification has so far not been undertaken 7 . The antigen CD30, while pathogonomonic in anaplastic large cell lymphoma, is universally expressed is several types of lymphoma, including classical Hodgkin lymphoma (cHL), but more recent studies identified it as a potential therapeutic target in B-cell non-Hodgkin lymphoma subtypes as well 8 . Brentuximab vedotin as a potential targeted therapeutic approach is a monoclonal CD30 antibody-drug conjugate (monomethyl auritatine E), which is already approved, due to encouraging results for several indications, including relapsed and refractory (cHL) and CD30positive peripheral T-cell lymphoma 9,10 .…”
Section: Dear Editormentioning
confidence: 99%